Control and Tracking Techniques for Switched Reluctance Machines - Calixto, Wesley Pacheco; Araújo, Wanderson Rainer Hilário; Morais, Lucas Diniz Silva; Reis, Marcio Rodrigues Cunha (Power Systems, 2025)
XXVIII, 172 p. 144 illus., 122 illus. in color.